Fisheries Oceanography: The first 30 years and new challenges in the 21st century. (15th December 2022) - Bograd, Steven J.; Edwards, Martin; Ito, Shin‐ichi; Nye, Janet; Chappell, Emily
Abstract: The journal Fisheries Oceanography provides a global forum for fisheries scientists and oceanographers to understand how marine ecosystems, and the services they provide to society, are structured and shaped by environmental variability and climate change. With this special issue, as well as the 30th Anniversary Virtual Issue of the most influential papers from the journal's history, we commemorate 30 years of publishing leading research in the field of fisheries oceanography. These issues showcase the extent, depth and impact of the research published in Fisheries Oceanography . We also reflect on the evolution of research themes through the journal's history, and highlight key emergent themes in our field. We look forward to continuing to publish impactful research in the pages of Fisheries Oceanography in the years ahead.